Investigating the resistance status to permethrin and temephos in Aedes aegypti (the yellow fever mosquito) - Arthur, Nicholas Wynne, author; Norton, Andrew, advisor; Camper, Matt, committee member; Kading, Rebekah, committee member; Saavedra-Rodriguez, Karla, committee member (Colorado State University. Libraries, 2024)
Aedes aegypti (Ae. aegypti) is the principle urban vector of several viruses of high medical significance which carry a disease burden on a global scale. Ae. aegypti is anthropophilic and lives in close association with humans. This places nearly half of the global population at risk of becoming infected with an arboviral pathogen every year. Therefore, emphasis must be placed on investigating methods for controlling this vector to combat and reduce the spread of human disease. This is especially true in areas where socioeconomic factors promote sustained transmission cycles. While vector control programs use a variety of strategies, the primary method of reducing vector populations is through insecticide use. Widespread use of insecticides has placed intense selection pressures on Ae. aegypti populations and resistance mechanisms have developed. Target site modifications and the expression of detoxifying enzymes are the most significant resistance mechanisms to date. Several single nucleotide polymorphisms resulting in amino acid changes within the voltage-gated sodium channel (VGSC) have been shown to reduce binding site sensitivity and confer resistance to pyrethroids. Specifically, mutations at the knockdown-resistant (kdr) 410, 1,016, and 1,534 sites have been associated with a reduction in pyrethroid sensitivity. I investigated the resistance status to permethrin and temephos at five locations in Hidalgo County, Texas. I determined the presence of permethrin resistance using a well-characterized susceptible colony as a reference for insecticide sensitivity. The resistant allele C1,534 reached fixation at all sites and L410 and I1,016 were found at high frequencies. The permethrin resistance was over 40-fold when compared to the reference colony. The sites were less resistant to temephos at approximately 6-fold to 12-fold, which I attributed to cessation of this insecticide in the continental United States since 2016. In the absence of selection pressures mosquito populations trend towards susceptibility, which suggests that there are potential fitness costs associated with insecticide resistance. Studying these associations is important to public health as they may support different strategies to reduce vector populations. I used two collections from Tapachula, Mexico, that were free of pyrethroid exposure since 2013, to determine the presence of two previously described fitness cost metrics: wing length and egg production. I found that the average wing length of V410L and V1,016I homozygous resistant individuals were significantly smaller compared to homozygous susceptible individuals. The interaction between wing length and genotype had no effect on egg production. Wing length had no significant effect on egg production. Most notably, L410 and I1,016 resistant alleles had no effect on egg production.